Quality of Environmental and Social Information Disclosure in Lithuanian Companies - Rudžionienė, Kristina; Bachtijeva, Diana (Information & Media, 2026)
Introduction. The disclosure of non-financial information by companies is gaining importance not only in terms of quantity but also quality. Therefore, this article aims to evaluate the dynamics of environmental and social disclosure quality among the largest Lithuanian companies during the transitional period of 2017–2024 prior to the mandatory application of ESRS. Disclosure quality is understood as the presentation of specific, numerical information in accordance with applicable standards. Methods. The study applies content analysis of publicly available annual reports and CSR/sustainability reports. Analysis. Based on the requirements of Directive 2014/95/EU, the GRI, and the ESRS, the completeness, specificity, and regulatory compliance of disclosures in reports of large public-interest entities were assessed. Results. During the analysed period, companies consistently moved from declarative to quantitative disclosure: the share of numerical information increased from 12% in 2017 to more than 70% in 2022–2023. The most significant change occurred prior to the introduction of the new regulation. Notably, environmental indicators are disclosed more frequently than social indicators. Conclusions. The results indicate that stricter regulation promotes the expansion of quantitative information; however, formal requirements alone do not ensure uniform disclosure content. The ESRS implementation reveals different levels of corporate preparedness.